MODEL LOCAL CULTURE TOURISM BERBASIS TANEAN LANJHANG DESA LARANGAN LUAR PAMEKASAN - Mansur Mansur; Ridan Muhtadi; Kamali Kamali; Akhmad Rofiki (JURNAL PROFIT, 2020)
This research aims to find the concept of local cultural tourism based on tanean lanjhang and applicable ways to preserve it by prioritizing the welfare of the surrounding community as well as in a sustainable manner. This qualitative-descriptive study collected data using in-depth interview techniques, participative observation and documentation. The result is that the field of local culture tourism does not only rely on tanean lanjhang, the Nurun Tajalla mosque, the sacred tomb of Bhujuk Jepara, mandhapa, tomang handicrafts and Nyato springs, but on reflection-products in the deepest contents of people's awareness. Preserving culture is ancestral fanaticism. Meanwhile, living in harmony, practice, economy, prosperity and sustainability in MICE-based regional tourism is local wisdom that deserves to be fought for and must be guarded by the Pamekasan authorities.